2010
DOI: 10.1353/dem.0.0085
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and excess mortality among the elderly in the United States and Mexico

Abstract: Increasing levels of obesity could compromise future gains in life expectancy in low- and high-income countries. Although excess mortality associated with obesity and, more generally, higher levels of body mass index (BAI) have been investigated in the United States, there is little research about the impact of obesity on mortality in Latin American countries, where very the rapid rate of growth of prevalence of obesity and overweight occur jointly with poor socioeconomic conditions. The aim of this article is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 39 publications
1
28
1
2
Order By: Relevance
“…An inverse U-shaped association was noted between educational levels and obesity status in the logistic regression models, which differs somewhat from other research that finds obesity being much more concentrated among lower SEP groups in Mexico [35,36]. A similar association found in this analysis has been noted between level of education completed and BMI among low-income Mexican adults [7].…”
Section: Discussioncontrasting
confidence: 65%
“…An inverse U-shaped association was noted between educational levels and obesity status in the logistic regression models, which differs somewhat from other research that finds obesity being much more concentrated among lower SEP groups in Mexico [35,36]. A similar association found in this analysis has been noted between level of education completed and BMI among low-income Mexican adults [7].…”
Section: Discussioncontrasting
confidence: 65%
“…In some low- and middle-income countries, low SES groups may now have sufficient access to cheap, calorie-dense, and processed food to put on excess weight (Drewnowski, 2007; Monteverde et al, 2010). A nutrition transition in developing societies has increased worldwide consumption of highly processed foods through exports, advertising, and the globalization of the agri-food system (Hawkes, 2006; Popkin, 2006).…”
Section: Explanations Of the Reversalmentioning
confidence: 99%
“…In a study of 36 low- and middle-income countries, the number of overweight persons exceeded the number of underweight persons in well over half (Mendez, Monteiro, & Popkin, 2005). For example, sharp increases in obesity have occurred in Mexico, even among the poorest segments of the population (Monteverde, Noronha, Palloni, & Novak, 2010), and more than a fifth of the adult population is overweight in China, with levels rising particularly among the poor (Popkin, 2008). The global trend toward excess weight means that low- and middle-income countries face a dual health burden – they must grapple with acute and infectious diseases at the same time that chronic medical conditions associated with obesity such as diabetes, hypertension, metabolic syndrome, and disability are rising (Chopra, Galbraith, & Darnton-Hill, 2002; Kelishadi, 2007; Popkin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent studies based on a series of national health surveys 12 and a group of older Americans 13,14 have concluded that the US obesity epidemic is not sufficient to reverse long-term trends in rising life expectancy. If such predictions are used as the basis for public policy, they could undermine efforts to prevent childhood and adult-onset obesity and its escalating negative effects on health and longevity.…”
Section: Two-dimensional Forecastingmentioning
confidence: 99%